2016
DOI: 10.1093/hsw/hlw057
|View full text |Cite
|
Sign up to set email alerts
|

In-home Smoking in Households with Women of Reproductive Age in Nepal: Does Women's Empowerment Matter?

Abstract: Authors examined the prevalence and predictors of in-home smoking in households with women of reproductive age. They analyzed data from 9,837 ever married women from 2011 Nepal Demographic Health Survey. About 17 percent of women and 66 percent of their husbands smoked and 58 percent of the women lived in homes that permitted in-home smoking. About 6 percent of the women were pregnant and 42 percent had given birth within the past five years. In-home tobacco use was equally prevalent in homes with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is reported that pregnant women are consistently exposed to home smoking in many countries, especially in the developing countries where legislations on active and passive smoking are rather weak. High number of pregnant women exposed to home smoking is also reported from Asian countries including Bangladesh [26].…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that pregnant women are consistently exposed to home smoking in many countries, especially in the developing countries where legislations on active and passive smoking are rather weak. High number of pregnant women exposed to home smoking is also reported from Asian countries including Bangladesh [26].…”
Section: Methodsmentioning
confidence: 99%